2019
DOI: 10.3390/cancers11040460
|View full text |Cite
|
Sign up to set email alerts
|

Cx43 Expression Correlates with Breast Cancer Metastasis in MDA-MB-231 Cells In Vitro, In a Mouse Xenograft Model and in Human Breast Cancer Tissues

Abstract: Connexins regulate multiple cellular functions and are considered tumor suppressors. Connexin43 (Cx43) is frequently down-regulated in breast tumors. However, Cx43 regulation during cancer onset and metastasis is complex and context-dependent. We investigated the effect of Cx43 over-expression or knock-down on the metastatic potential of MDA-MB-231 breast cancer cells in vitro and in vivo and in human breast cancer tissues. MDA-MB-231 cells over-expressing (Cx43D) or down-regulating Cx43 (shCx43) were generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…It has been reported that in brain metastases derived from breast cancer the up-regulation of MYC participates in the recruitment of macrophages and plays an important role in the formation of gap junctions between metastatic cells and astrocytes, which seems crucial for the metastatic growth within the brain [ 198 ]. MYC takes part in the generation of gap junctions through the up-regulation of Connexin 43 (Cx43), a crucial protein in favoring close interactions between cancer cells and endothelial cells, hence, facilitating extravasation and local survival of metastatic cells [ 198 , 199 ]. The correlation between the up-regulation of Cx43 and metastasis is reported not only in breast cancer, but also in prostate cancer, where the increased expression of Cx43 is involved in bone-specific metastasis, the most common target site for advanced prostate cancers [ 200 ].…”
Section: Myc–the Regulator Of Emt and Metastasismentioning
confidence: 99%
“…It has been reported that in brain metastases derived from breast cancer the up-regulation of MYC participates in the recruitment of macrophages and plays an important role in the formation of gap junctions between metastatic cells and astrocytes, which seems crucial for the metastatic growth within the brain [ 198 ]. MYC takes part in the generation of gap junctions through the up-regulation of Connexin 43 (Cx43), a crucial protein in favoring close interactions between cancer cells and endothelial cells, hence, facilitating extravasation and local survival of metastatic cells [ 198 , 199 ]. The correlation between the up-regulation of Cx43 and metastasis is reported not only in breast cancer, but also in prostate cancer, where the increased expression of Cx43 is involved in bone-specific metastasis, the most common target site for advanced prostate cancers [ 200 ].…”
Section: Myc–the Regulator Of Emt and Metastasismentioning
confidence: 99%
“…Real-Time Cell Analysis (RTCA) was used to study invasion and proliferation of MDA-MB-231 and MDA-PANX1cells. Cells were seeded on a cellular invasion plate (CIM-plate 16) with micro-electronic sensors on the underside of an 8 µm microporous polyethylene terephthalate membrane [18,[96][97][98] of a Boyden-like upper chamber, and real-time evaluation of cell impedance was performed using xCELLigence RTCA [A2] DP instrument (Roche). For invasion assays, 30 µL of growth factor-reduced Matrigel TM (BD Biosciences, San Jose, CA, USA) diluted in serum-free medium at a ratio of 1:20 were used to coat the upper surface of the membrane, followed by incubation at 37 • C in 5% CO 2 for 4 h in a humidified incubator and then washed with PBS.…”
Section: Invasion and Proliferation Assaysmentioning
confidence: 99%
“…Cardiac‐specific loss of N‐cadherin leads to lethal arrhythmogenesis and dissolution of the ID structure, with a significance decrease in the expression of Cx43 and Cx40 (Kostetskii et al, ; Li et al, ). However, Cx43 knockdown promotes N‐cadherin expression in MDA‐MB‐231 breast cancer cells in vitro (Kazan et al, ). The present study demonstrated that LRP6‐CKO induced a sharp decrease in Cx43 expression, which may contribute to the increased N‐cadherin expression in LRP6‐deficient hearts.…”
Section: Discussionmentioning
confidence: 99%